Socioeconomic disadvantage and polygenic risk of overweight in early and mid-life: a longitudinal population cohort study spanning 12 yearsResearch in context - Jessica A. Kerr; Dorothea Dumuid; Marnie Downes; Katherine Lange; Meredith O'Connor; Ty Stanford; Lukar Thornton; Suzanne Mavoa; Kate Lycett; Tim S. Olds; Ben Edwards; Justin O'Sullivan; et al. (Elsevier, 2024)
Summary: Background: We describe BMI by socioeconomic disadvantage and by polygenic risk in parallel cohorts of children and adults (their parents). We examine whether hypothetically intervening to reduce childhood disadvantage could reduce adolescent obesity. Methods: From a population-based cohort (N = 5107) with a mixed design (survey and direct assessment), 24-31% had genotype data: 1607 children (50% male) followed biennially from age 2-3 to 14-15; 2406 adults (36% male) followed from mean age 35-47 years. Exposures were polygenic risk score for BMI, and neighbourhood- and family-level socioeconomic disadvantage categorised as 'most' (top two cohort-specific quintiles), 'average', or 'least' disadvantage (bottom two quintiles). We explored trends in estimated BMI and risk of overweight/obesity by disadvantage, stratified by polygenic risk. We used generalised linear regression to estimate the reduction in overweight/obesity at 14-15 years in children living in 'least/average disadvantage' in early childhood relative to those in 'most disadvantage', adjusted for confounders. Causal effect estimates were obtained separately for children with higher and lower polygenic risk. Findings: A positive trend between disadvantage and overweight/obesity was most apparent among participants with high polygenic risk. Among children with higher polygenic risk (n = 805), hypothetical target trial results imply that intervening to lessen population-wide neighbourhood disadvantage from most to least disadvantage could reduce adolescent overweight/obesity by 32% (risk ratio (RR) 0.68, 95% CI 0.50-0.92), or by 42% if intervening to lessen family disadvantage (RR 0.58, 95% CI 0.42-0.79). Positive effects were smaller when isolating the population to those with lower polygenic risk (7-17%), and for the whole population, regardless of polygenic risk (25-39%). Interpretation: Children at higher polygenic risk of obesity suffer disproportionate BMI impacts of disadvantage. At the population-level, and especially for those with higher polygenic risk, tackling disadvantage could potentially reduce obesity and associated morbidity, mortality, and costs. Funding: Australian National Health and Medical Research Council. Funding information is detailed in the funding statement.